VISITORS' PERCEPTION OF THE SOCIAL AND EDUCATIONAL FUNCTIONS OF TAMAN CERDAS SAMARINDA AS A PUBLIC SPACE - Siti Muflihah; Nurul Azmi; Yulian Widya Saputra; Mei Vita Romadon Ningrum (UNIVERSITAS SEBELAS MARET (UNS), 2025)
Urban growth and population expansion have heightened the demand for public spaces with sufficient facilities and infrastructure to support diverse recreational activities. Taman Cerdas Samarinda, developed by the government, serves as a public space intended to meet community needs. This study examines the effectiveness of Taman Cerdas Samarinda in fulfilling its social and educational functions. The objective is to identify and analyze visitors’ perceptions regarding these roles. A descriptive quantitative research method was employed, incorporating observation, interviews, questionnaires, and documentation. Findings indicate that the social function of Taman Cerdas Samarinda, as perceived by visitors, is adequately fulfilled, achieving a score of 79% (categorized as good). The educational function is also perceived as effective in fostering environmental literacy, with a score of 76% (good).